2019
DOI: 10.1097/md.0000000000016889
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty in a patient with ipsilateral hip ankylosis

Abstract: Rationale:There is a large number of people that have knee degeneration in China. Total knee arthroplasty is one of the most effective methods of treatment in the later stages of the disease. However, there are challenges when performing total knee arthroplasty on patients with ipsilateral hip akylosis. So far, there are few reports on postoperative curative effect of total knee arthroplasty for these patients. This case report records how to perform total knee arthroplasty in a patient with ipsilateral hip an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Previously reported good outcomes support the benefit of TKA regardless of whether the prior hip arthrodesis was left in place or converted to total hip arthroplasty before TKA [ [1] , [2] , [3] , [4] , [5] ]. Conversion of a hip fusion to total hip arthroplasty itself is a technically demanding procedure with a relatively high complication rate and may not be necessary before considering TKA [ 5 , 7 ].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previously reported good outcomes support the benefit of TKA regardless of whether the prior hip arthrodesis was left in place or converted to total hip arthroplasty before TKA [ [1] , [2] , [3] , [4] , [5] ]. Conversion of a hip fusion to total hip arthroplasty itself is a technically demanding procedure with a relatively high complication rate and may not be necessary before considering TKA [ 5 , 7 ].…”
Section: Discussionmentioning
confidence: 93%
“…TKA is one of the most common and successful surgical interventions provided by orthopaedic surgeons, which includes patients with prior ipsilateral hip arthrodesis [ [1] , [2] , [3] , [4] , [5] ]. Romness and Morrey previously demonstrated good outcomes for their case series of patients with prior ipsilateral hip arthrodesis or ankylosis with or without takedown of the fusion and conversion to total hip arthroplasty before knee replacement, with their focus on patient outcomes rather than technical guidance [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have suggested using a sandbag under the ipsilateral buttock [7] or elevating the fused hip joint to allow the knee to flex up to 100° on the operating table, with a good surgical outcome. Alternatively, the patient can be positioned supine at the bottom of the table, allowing the knee to bend from the end of the operating table [15]. Another approach proposes elevation of the patient's upper body and contralateral leg and using a mobile leg positioner to facilitate exposure [11].…”
Section: Introductionmentioning
confidence: 99%